2003
DOI: 10.1007/s11842-003-002-x
|View full text |Cite
|
Sign up to set email alerts
|

Joint ventures in private forestry in Ireland

Abstract: A study was conducted with the objective of obtaining a profile of farmers who have participated in the Farm Partnership Scheme in Ireland. This scheme is a joint venture between Coillte (The Irish Forestry Board) and farmers. Under the terms of the scheme, Coillte is responsible for the establishment, management and harvesting of the forest plantation on the farmer's land. The farmer retains ownership of the land, receives premium payments and shares in the harvesting profits. Fifty farmers who joined the Far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Another advantage of encouraging past planters to afforest more land would be that larger forests might be created when planting fields adjacent to the previously planted areas. Our own previous research, as well as other studies, had shown that farmers would only afforest 'bad land' (Collier et al, 2002;Frawley, 1998;Frawley and Leavy, 2001;Hannan and Commins, 1993;Kearney, 2001;McCarthy et al, 2003;Ní Dhubháin and Gardiner, 1994;Ní Dhubháin and Kavanagh, 2003). Further research could reveal whether past planters intend to afforest remaining patches of 'bad land' or, if due to a positive afforestation experience, they would consider planting even better quality land, which would indicate an improvement in the attitude towards forestry as a farm enterprise.…”
Section: Farmers Considering Afforestationmentioning
confidence: 79%
See 1 more Smart Citation
“…Another advantage of encouraging past planters to afforest more land would be that larger forests might be created when planting fields adjacent to the previously planted areas. Our own previous research, as well as other studies, had shown that farmers would only afforest 'bad land' (Collier et al, 2002;Frawley, 1998;Frawley and Leavy, 2001;Hannan and Commins, 1993;Kearney, 2001;McCarthy et al, 2003;Ní Dhubháin and Gardiner, 1994;Ní Dhubháin and Kavanagh, 2003). Further research could reveal whether past planters intend to afforest remaining patches of 'bad land' or, if due to a positive afforestation experience, they would consider planting even better quality land, which would indicate an improvement in the attitude towards forestry as a farm enterprise.…”
Section: Farmers Considering Afforestationmentioning
confidence: 79%
“…Similarly McDonagh et al (2010) discovered that the main barriers to planting for Irish farmers was the inflexibility resulting from afforestation and their assertion that they needed all their land for agriculture. A number of earlier studies similarly found that the majority of farmers only considered afforesting land that could not be used agriculturally or that was 'good for nothing else' (Collier et al, 2002;Frawley, 1998;Frawley and Leavy, 2001;Hannan and Commins, 1993;Kearney, 2001;McCarthy et al, 2003;Ní Dhubháin and Gardiner, 1994;Ní Dhubháin and Kavanagh, 2003).…”
Section: Factors Influencing Farmers' Afforestation Decisionsmentioning
confidence: 99%
“…Alternative employment options could be offered by a strong sustainable forestry and wood-processing sector, as the natural conditions in Ireland are very favourable to tree growth (DAFF, 1996(DAFF, , 2010. The mean annual increment is approximately twice as high as that in mainland Europe (Kearney and O'Connor, 1993;Ní Dhubháin and Kavanagh, 2003). Forests, however, cover only approximately 11% of Ireland's land surface, far less than the European average of 40% (EUROSTAT, 2011).…”
Section: Farm Afforestation Policies In Irelandmentioning
confidence: 99%